NPD DEPICTION ON DONALD TRUMP IN THE DEBATE WITH KAMALA HARRIS: CONTENT ANALYSIS DESIGN - Yules Sianipar; Megarizky Hotmauli; Gunawan Tambunsaribu; Teguh Prasetyo (Prodi Sastra Inggris UKI, 2025)
Narcissistic Personality Disorder (NPD) is a symptom of someone considering themselves superior to others, thirsting for praise from others, and having little or no empathy for others. we can use the acronym SPECIAL ME to remember the nine traits of NPD: Sense of self-importance, Preoccupation with power, beauty, or success, Entitled, Can only be around important people, Interpersonally exploitative for their gain, Arrogant, Lack empathy, Must be admired, Envious of others or believe that others are envious of them. Many psychoanalytically oriented clinicians consider it a product of the current era and value system (A. W. Lestari, 2023). The research method used in this study is qualitative. The approach used in this study is phenomenological. Phenomenology; seeks to uncover, study, and understand phenomena and their unique contexts experienced by individuals to the level of beliefs of the individual concerned (Fadli, 2021). This study analyzes the transcript data of the debate between Trump and Harris using a content analysis design. According to Holsti, the content analysis method is a technique for concluding by objectively, systematically, and generally identifying various specific characteristics of a message (Astuti et al., 2023). The data source used is the script of the US presidential campaign debate between Donald Trump and Kamila Harris. From 110 data collected, 64 of Donald Trump's statements contain elements of a lack of empathy and arrogance. 47 data of Donald Trump's statements contain an exaggerated sense of self-importance, a need for admiration, Preoccupation with power, beauty, or success, Entitled, Arrogant, and Must be admired. This tendency can be seen in Donald Trump's statements during the presidential debate with Kamala Harris, either in answering questions from the host or responding to statements from Kamala Harris.